Immunogenicity and safety of Vero cell culture-derived Japanese encephalitis vaccine: a phase 3 study in Chinese infants - Huanhuan Wang; Juan Wang; Shijie Yan; Gengfan Zhao; Shanzhen Wang; Hong Tao; Ye Xu; Jinfeng Wu (Taylor & Francis Group, 2024)
Background Japanese encephalitis (JE) is a severe infectious disease of the central nervous system. Vaccination with Vero cell culture-derived vaccines may effectively reduce JE incidence.Research Design and Methods In this single-center, randomized, blinded, positive-controlled clinical trial in China involving 600 healthy infants aged 6-11 months, participants were divided into experimental and control groups administered JEV-PI and JEV-LI, respectively. Antibody titers were determined after 0- and 7-day immunization schedules. A booster dose followed 12 months later.Results After primary vaccination and before booster vaccination, the positive conversion rate, geometric mean titer (GMT), and geometric mean increase (GMI) of JEV-PI-neutralizing antibodies exceeded those of JEV-LI. After booster immunization, the GMT and GMI of JEV-PI were higher than those of JEV-LI. After primary immunization, the local, systemic, and overall adverse reactions were of grades 1 and 2, with a low incidence of grade 3. After booster immunization, these differences were mainly grades 1 and 2, with no differences between JEV-PI and JEV-LI.Conclusion JEV-PI is a promising vaccine as infants acquired long-lasting and highly neutralizing immune antibodies after inoculation with JEV-PI.Trial Registration The trial was registered in the Chinese Clinical Trial Registry (https://www.chictr.org.cn/showproj.html?proj = 203130; registration number: ChiCTR2300074692; registration date: 14/08/2023).